THE FACTORS OF HINDU COUNSELORS DYNAMICS IN SPECIAL CAPITAL REGION OF JAKARTA - suhardi, untung; I Made Kartika Dhiputra; Wayan Paramarta (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
The existence of counselors in Special Capital Region of Jakarta is following the regulation of the Ministry of Religion in carrying out guidance following their duties and functions. The development of globalization is moving very fast both in technology and science. This acceleration is related to the digital era and the state of culture. However, the implementation of guidance carried out by the counselors in Jakarta is still experiencing dynamics, especially in the factor of the dynamics of the counselors. This study uses a phenomenological approach and an interpretive paradigm including the types of data, data sources, primary data sources, and secondary data sources. In this study, the data was analyzed through data reduction, data presentation, and data verification. This study implemented the theory of public spaces. The results of this study indicate that the first factor of the dynamics of religious instructors is internal factors; extension education, understanding of Hinduism, tasks, and challenges of life. Secondly, the external factors; dialectics of communication and the development of information technology, adjustment, and ethical tolerance of extension workers. This is as a self-help extension in life to guide a form of applying devotional values ​​to Hyang Widhi Wasa.